Conceptual Metaphors in Stock Market Reports in the Malaysian Business Times - Tengku Mahmood, Tengku Farah Petri (2010)
The purpose of this study is to identify the metaphorical linguistic expressions of conceptual metaphors in the Malaysian Business Times using Charteris-Black and Ennis’ (2001) proposed list of conceptual metaphors. This study is a non-experimental descriptive study, which uses the corpus linguistic approach for data collection and the corpus for analysis of 50 share market news reports that were randomly identified. An expert within the business context was appointed to provide expertise in the interpretation of specific types of data derived from the corpus. The findings demonstrate that the conceptual metaphors: MARKET MOVEMENTS ARE PHYSICAL MOVEMENT and THE ECONOMY IS AN ORGANISM are the most dominant conceptual metaphors found in the corpus collected. In addition, the findings show that the metaphorical linguistic expressions generally concretise the abstract concept of the economy and market movements. Findings from this study suggest that conceptual metaphors could enhance language learners’ creativity in language learning by having a better grasp of the course subjects in terms of underlying concepts of metaphors used, hence developing an understanding of how conceptual metaphors work (Sharifah Hafizah 2004). This study has also developed a step-by-step procedure in identifying metaphorical linguistic expressions. With this newly-developed method, it is hoped to facilitate future studies in identifying metaphorical linguistic expressions.